Detecting a rare composite small bowel lymphoma by Magnetic Resonance Imaging coincidentally: A case report with radiological, surgical and histopathological features. (2018) - Pezzella, M.; Brogna, B.; Romano, A.; Torelli, F.; Esposito, G.; Petrillo, M.; Romano, F.M.; Di Martino, N.; Reginelli, A.; Grassi, R.
Highlights: Diagnosis of gastrointestinal lymphoma can be occasionally challenging. Composite lymphomas are rare presentations of gastrointestinal lymphoma. Lymphoma histology can be multifaceted. Magnetic Resonance Imaging provides high diagnostic yields. With bulky mass, surgery can be useful before chemotheraphy to prevent bowel perforation (Reference n 22). Abstract: Introduction: Diagnosing lymphoma continues to prove challenging in the clinical practice. Composite lymphoma (CL) is defined by the coexistence of different lymphoma subtypes in the same anatomical location. This condition has seldom been witnessed in the gastrointestinal (GI) tract. We weren't able to find previous cases in the literature about small bowel CL with follicular lymphoma (FL) and classical Hodgkin lymphoma (CHL). Surgery is the treatment of choice to obtain accurate histology, to manage and prevent acute complications. We state that this work has been reported in line with the SCARE criteria. Case presentation: We describe an extremely rare case of small bowel CL, presenting as an intestinal bulky mass with circumferential infiltration of bowel loops. The small bowel tumor was incidentally detected by abdominal Magnetic Resonance Imaging (MRI) in a 64-year-old man who suffered from rectal discomfort and non-specific clinical symptoms. After this radiological finding, the patient underwent multiphase contrast computed tomography (MDCT) for initial staging and to study vascular involvement. Surgery was recommended to obtain an accurate diagnosis both due to initial symptoms of the intestinal obstruction and to avoid small bowel complications. The histopathological examination revealed a small bowel CL composed mainly of B cells FL with also CHL components. Conclusion: It is important to note that involvement of the proximal ileal loops is very rare in small bowel lymphoma. MRI represents a precious diagnostic tool to evaluate the intra and extramural extent of the tumor.